India' foreign policy: the democracy dimension - "Muni, S.D" (Delhi, 2009)
In the new millennium, India has joined global initiatives like the Community of Democracies (2000) and the UN Democracy Fund (2005) for promoting democracy. This marks a significant shift in India 's foreign policy as never earlier had India claimed or committed itself to playing a proactive role in promoting and protecting democracy in other countries. India has always remained engaged with the democracy question, particularly in its immediate neighbourhood. India's Foreign Policy: the Democracy Dimension is a study of India's responses to the challenge of democracy in other countries before and after its participation in the global democratic initiatives. India's similar responses in the past have been dictated and defined by its perceived vital strategic and political interests, and this continues to be so. The newly acquired obligations for promoting democracy may have tempered its foreign policy rhetoric and style on the democracy question but it has not, and will not, override India's critical strategic concerns and interests
Keywords: Foreign relations-India